2016
DOI: 10.1590/s0102-865020160120000004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sılymarın on oxıdatıve stress and lıver hıstopathology ın experımental obstructıve jaundıce model

Abstract: PURPOSE:To investigate the effect of silymarin on oxidative stress and hepatic injury induced by obstructive jaundice in an experimental model. METHODS:Thirty Wistar-Albino type female rats were divided into 3 groups each including 10 rats. Only laparotomy was performed in group 1. Bile duct ligation was performed in group 2. In group 3, bile duct ligation was performed and orogastic silymarin 300 mg/ kg/day dose was given for seven days. At the end of seven days, rats were sacrificed. The blood and liver tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…In the present study, induction of liver fibrosis in Wistar male albino rats was done by injection with carbontetrachloride (CCl4) (2 ml/kg body weight, dissolved in olive oil [1:9(v/v)] by intraperitoneal (i.p) injection twice a week for 8 weeks (12) .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, induction of liver fibrosis in Wistar male albino rats was done by injection with carbontetrachloride (CCl4) (2 ml/kg body weight, dissolved in olive oil [1:9(v/v)] by intraperitoneal (i.p) injection twice a week for 8 weeks (12) .…”
Section: Discussionmentioning
confidence: 99%
“…After the surgical procedures were completed, the rats were sacrificed on postoperative day 10, and liver tissue and blood samples were taken. The obstructive jaundice model in the study is a model that has been widely used by both our team members and other researchers [12][13][14] .…”
Section: Methodsmentioning
confidence: 99%
“…Freitag et al (46) reported that silymarin treatment has restored the hepatocyte functional and histopathological alterations induced by paracetamol in normotensive and hypertensive animals. In another study of experımental obstructıve jaundice model, the enlargement of hepatocytes, dilatation of canaliculi and the edema regressed in livers in the silymarin--treated group was reported (47).…”
Section: Macroscopical and Histopathological Assessmentmentioning
confidence: 95%